Factors Influencing Customers' Purchase Intention in Social Commerce - Abou Ali, Ali; Abbass, Alaa; Farid, Nihal (International Review of Management and Marketing, 2020)
This paper inspects the relationship between purchase intention in social media context and relevant factors namely: trust, perceived risk, online behavioral advertising, and social commerce constructs. Using judgmental sampling technique, 384 questionnaires across Lebanon were collected and analyzed using structural equation modeling (SEM). The results show that purchase intention of the respondents is significantly positively affected by social commerce constructs, trust, and online behavioral advertising. And trust is positively enriched by social commerce constructs. Also, it is clear that positive social commerce constructs will decrease the perception of risks between customers when shopping online. Perceived risk influence on purchase intention is not significant, Trust negatively impacts perceived risk. This paper shows specific inferences about the factors affecting buying intention in social commerce. It provides fruitful insights to both academic researchers and professional marketers. In terms of limitations, other factors might be added and be under examination; that might include value perceptions, social presence, social proof, and artificial intelligence agents such as Facebook chatbots. In addition, other product categories are useful to get more insights about the intentions of customers; such as cosmetics, home appliances, phones, and other service industries as cleaning, laundry, financial services, etc. The study attempted to examine potential factors to evaluate the purchase intentions (PI) in the social commerce context in Lebanon. It extends the earlier literature by providing clues about the positive influence of OBA on PI. Keywords: Social Commerce, Online Behavioral Advertising, Trust, Perceived Risk, Purchase intention. JEL Classifications: L81, M3 DOI: https://doi.org/10.32479/irmm.10097